Моделирование механизмов возникновения нестабильности сложных систем - Атоев, К.Л.; Пепеляев, В.А. (Теорія оптимальних рішень, 2007)
The main objective of the work is to strengthen the capacity in study of uncertainty impact on security of complex systems for which standard modeling methods are inadequate. The regimes with sudden, discontinuous changes that cause the instability have been modeling for a wide range of different complex systems from economics and ecology to sociology and biology.